PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA KERJA TERHADAP KINERJA KARYAWAN PADA PT BANDUNG SCIENTIFIC TECHNICAL INDONESIA DI JAKARTA PUSAT - Wika Wijaya; Ana Septia Rahman (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the effect of the work environment on employee performance, to understand the impact of work discipline on employee performance, and to assess the combined effect of the work environment and work discipline on employee performance. This research uses a quantitative approach with a sample of 50 respondents who are employees of PT Bandung Scientific Technical Indonesia. Data collection techniques include primary and secondary data. Data analysis techniques involve descriptive analysis, validity and reliability tests, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, linear regression analysis, correlation coefficients, coefficient of determination analysis, t-test, and F-test. The analysis was conducted using SPSS, with the following research results: The work environment does not have an effect on the performance of employees at PT Bandung Scientific Technical Indonesia in Central Jakarta. This is evidenced by the t-count value > t-table or (1.904 < 2.011). This is also supported by the Sig value, <0.05 or (0.63 > 0.05). Work discipline significantly affects the performance of employees at PT Bandung Scientific Technical Indonesia. This is evidenced by the t-count value > t-table or (3.138 > 2.011). This is also supported by the Sig value, <0.05 or (0.03 < 0.05). The work environment and work discipline simultaneously have a significant effect on employee performance with the regression equation Y = 8.553 + 0.283X1 + 0.451X2. The coefficient of determination is 43.9%, while the remaining 37.2% can be influenced by other factors. The hypothesis test shows an F-count value > F-table or (18.390 > 2.800).